Assessing habitat suitability and selecting optimal habitats for relict tree Cathaya argyrophylla in Hunan, China: Integrating pollen size, environmental factors, and niche modeling for conservation - Fen Xiao; Yuchen She; Jiyun She; Jinmei Zhang; Xin Zhang; Chuying Luo (Ecological Indicators, 2022)
The endangered plant Cathaya argyrophylla Chun et Kuang is the only species in the genus and is endemic to China, and because of challenged regeneration and shrinking habitats, the protected areas (PAs) need to be expanded in Hunan Province. In this study, a maximum entropy model (MaxEnt) was used to predict the potentially suitable habitats and population centroid migrations for C. argyrophylla in Hunan under four climate change scenarios (SSP1-2.6, SSP2-4.5, SSP3-7.0, and SSP5-8.5) at four time points (2030, 2050, 2070, and 2090) based on thirteen environmental variables. For the first time, optimal habitats that could support breeding Cathaya populations with good fruiting quality in Hunan were identified considering relations between pollen grain size and environmental variables. Of the total area, 10.69 % (22.63 × 103 km2) was suitable for C. argyrophylla, which was distributed primarily in western and southern parts of Hunan. Monthly precipitation in August was the environmental variable that contributed the most (28.2 %) to C. argyrophylla distribution. Other influential variables were annual mean temperature, annual precipitation, mean temperature of the wettest quarter, monthly solar radiation in May, and precipitation of the driest month. The suitable distribution area for C. argyrophylla decreased overall under the climate change scenarios, with SSP2-4.5 the exception. Population centroid of C. argyrophylla shifted overall slightly toward southeast areas with more abundant precipitation in Hunan under climate change. The average shift distance was 3.89 km, and the longest migration distance (8.84 km) was in 2090 under SSP1-2.6. In Hunan, 642.12 km2 were authority identified as optimal habitat based on the current climate. It is proposed that areas with altitudes between 758 m and 1,500 m be treated as crucial PAs networks for C. argyrophylla, mainly including Nanyue, Yanling, Guidong, Xinning, and Zixing counties and districts. The goal of the study was to assist in the conservation and management of C. argyrophylla, but it also provides an example of how to evaluate optimal habitats for those endangered species that need to produce populations with specific superior characteristics.